EU Asylum Policies & the Greek Presidency: an EU Opportunity - Baxevanis, Christos; Papadaki, Maria (Études helléniques / Hellenic Studies, 2014)
The Hellenic Presidency, among others, focuses its efforts on a European holistic approach and management of the migration policy. EU Asylum Policy has been a controversial topic for more than a decade. Following a period of policy harmonisation, the EU has reached a crucial stage in the development of a new Common European Asylum System. 2012-2013 was a defining period in the process of adopting the new ‘Asylum Package’, i.e., the revision of the legal instruments that comprise the EU asylum acquis. At the national level, several Member States, such as Greece, made major changes to their asylum systems in 2012, some of which were the result of pressures such as large numbers of applications, limited capacity to process applications, systemic deficiencies, or a combination of these and other factors. In Greece, it has been established new administrative bodies responsible for registration of applications for international protection, status determination, reception and appeal. The radical reform of the asylum system will not only entail a fair treatment of refugees, but will bring important benefits to Greece. It will reinforce the country’s influence and ability to negotiate at the EU level changes in European policies.